2013
DOI: 10.5194/acp-13-11951-2013
|View full text |Cite
|
Sign up to set email alerts
|

Gravity wave influence on NLC: experimental results from ALOMAR, 69° N

Abstract: Abstract. The influence of gravity waves on noctilucent clouds (NLC) at ALOMAR (69 • N) is analysed by relating gravity wave activity to NLC occurrence from commonvolume measurements. Gravity wave kinetic energies are derived from MF-radar wind data and filtered into different period ranges by wavelet transformation. From the dataset covering the years 1999-2011, a direct correlation between gravity wave kinetic energy and NLC occurrence is not found, i.e., NLC appear independently of the simultaneously measur… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 51 publications
0
4
1
Order By: Relevance
“…Note that this increase in correlation coefficient is also seen when the correlations are calculated by removing the background signal (i.e., the underlying smoothly variable seasonal signature) implying that the seasonal time scale does not dominate the higher correlation coefficients. The positive correlations contradict Wilms et al (2013), who reported that PMCs over Alomar (69°N) did not correlate with simultaneous measurements of GW kinetic energy at the same altitude. They concluded that the PMCs over ALOMAR, which is at the lower limit of the latitudes (~60–85°N) observed by SOFIE, were advected horizontally and not affected by co‐located GWs.…”
Section: Resultscontrasting
confidence: 89%
See 2 more Smart Citations
“…Note that this increase in correlation coefficient is also seen when the correlations are calculated by removing the background signal (i.e., the underlying smoothly variable seasonal signature) implying that the seasonal time scale does not dominate the higher correlation coefficients. The positive correlations contradict Wilms et al (2013), who reported that PMCs over Alomar (69°N) did not correlate with simultaneous measurements of GW kinetic energy at the same altitude. They concluded that the PMCs over ALOMAR, which is at the lower limit of the latitudes (~60–85°N) observed by SOFIE, were advected horizontally and not affected by co‐located GWs.…”
Section: Resultscontrasting
confidence: 89%
“…More recently, Wilms et al (2013) used common volume lidar and radar data over Andenes, Norway (69.3°N, 16°E), to study the correlation between NLC occurrence observed by lidar and GW kinetic energy derived from radar wind data at NLC altitudes. They reported no correlation and discussed the possibility that the observed NLCs might have been advected horizontally (Gerding et al, 2007), and therefore, the common volume GWs might not have had any influence on the formation of the observed NLCs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These techniques cover certain height ranges and resolve different vertical, horizontal and timescales (Gardner and Taylor, 1998): lidar technique for observation from the troposphere up to the mesosphere (e.g., Gardner et al, 1989;Rauthe et al, 2008;Li et al, 2010), limb sounding satellites from the stratosphere up to the lower mesosphere (e.g., Alexander et al, 2008), radars from the upper troposphere/lower stratosphere or the mesosphere (e.g., Réchou et al, 2013;Wilms et al, 2013), OH-Imagers from the upper mesosphere/lower thermosphere (e.g., Walterscheid et al,…”
Section: Introductionmentioning
confidence: 99%
“…There are many waves in the troposphere and lower stratosphere (TLS) (3-23 km), such as gravity waves, Kelvin waves, planetary waves, and tidal waves, which play very important roles in energy transmission and atmospheric composition movements (Wilms et al, 2013). Various detection systems and physical models have been used to study atmospheric oscillations and waves, particularly the generation and propagation of the inertia gravity waves (IGWs) (Uccellini and Koch, 1987;Wu and Waters, 1996;Fritts and Alexander, 2003;Zülicke and Peters, 2006;Wang and Zhang, 2010;Swales et al, 2012;Vadas and Nicolls, 2012;Hans et al, 2013;Geller et al, 2013;Murphy et al, 2014;Réchou et al, 2014;Placke et al, 2014;Plougonven and Zhang, 2014).…”
Section: Introductionmentioning
confidence: 99%